Neonatal Hyperoxia Exposure Induces Kidney Fibrosis in Rats - Jiunn-Song Jiang; Hsiu-Chu Chou; Tsu-Fu Yeh; Chung-Ming Chen (Elsevier, 2015)
Human and animal studies have demonstrated that neonatal hyperoxia increases oxidative stress and adversely affects glomerular and tubular maturity. This study was undertaken to determine how exposure to neonatal hyperoxia affected kidney morphology and fibrosis and to elucidate the relationship between connective tissue growth factor (CTGF) and collagen expression in rat kidneys. Methods: Sprague-Dawley rat pups were exposed to either hyperoxia or ambient air. The control groups were maintained in ambient air for 1 week and 3 weeks. The hyperoxia groups were exposed to >95% O2 for 1 week and subsequently placed in an environment of 60% O2 for an additional 2 weeks. The animals were euthanized on Postnatal Day 7 or 21 and the kidneys underwent histological analyses and oxidative stress and total collagen measurements. Results: The rats reared in O2-enriched air exhibited significantly higher tubular injury scores (1.4 ± 0.5 vs. 0.7 ± 0.7 on Day 7; 1.4 ± 0.5 vs. 0.6 ± 0.5 on Day 21), a larger proportion of the cortex occupied by glomeruli (25.5 ± 4.1 vs. 21.3 ± 3.1% on Day 7; 20.1 ± 3.5 vs. 17.1 ± 1.7% on Day 21), larger glomerular sizes (84.7 ± 5.8 vs. 77.5 ± 6.1 μm on Day 7; 88.4 ± 2.9 vs. 84.9 ± 3.1 μm on Day 21), and higher total collagen content (54.1 ± 27.5 vs. 18.3 ± 6.3 μg/mg protein on Day 7; 397.4 ± 32.8 vs. 289.5 ± 80.0 μg/mg protein on Day 21) than did rats reared in ambient air. Immunohistochemical expressions of oxidative stress marker 8-hydroxy-2'-deoxyguanosine and CTGF immunoreactivities were significantly higher in the rats reared in O2-enriched air compared with the rats reared in ambient air on Postnatal Days 7 and 21. Conclusion: Neonatal hyperoxia exposure contributes to kidney fibrosis, which is probably caused by activated CTGF expression.